المتخيل الصحراوي والسرد الرحلي في رواية "الملحد" لعبد الرشيد هميسي - ربح الله, ايمان; مناصر, نجاة (جامعة الوادي - University of Eloued, 2023)
تحاول هذه الدراسة الكشف عن المتخيل الصحراوي والسرد الرحلي من خلال رواية (الملحد)، للدكتور عبد الرشيد هميسي، حيث استطاع بلمسته الخاصة توظيف المتخيل الصحراوي وبيان قيمة الرحلة من خلال هذا العمل الروائي، وكشفت هذه الدراسة أهمية الصحراء كبيئة وفضاء دلالي لها، لما لها من خصوصية تنعكس على باقي مكونات العمل السردي، كم يضيء هذا البحث رواية توظيف الصحراء كمكان له خصائصه الجغرافية والروحية والاجتماعية، ويمتلك فضاء الصحراء خاصية تميزه، لذا كان لتجلي المتخيل الصحراوي نصيب كبير فيه، كما أن الصحراء هي منبع الرحلات، فالبيئة الصحراوية تمتاز بموروثها المادي والمعنوي الخاص، ليبقي الإنسان العربي ابن بيئته، وتكون الصحراء أيضا مكان يستقبل الزوار من كل مكان. summary: This study attempts to uncover the desert imagination and travel narrative through the novel "Al-Mulhid" (The Atheist) by Dr. Abdelrashid Hemissi. Through his unique touch، Hemissi was able to employ the desert imagination and articulate the value of travel through this literary work. The study reveals the importance of the desert as an environment and a symbolic space، as it has particular characteristics that are reflected in the other elements of the narrative work. This research sheds light on the novel's use of the desert as a place with its own geographic، spiritual، and social features. The desert space has a distinguishing property، and the desert imagination plays a significant role in it. Furthermore، the desert is the source of journeys، and the desert environment is characterized by its unique material and spiritual heritage، which keeps the Arab human connected to his environment. The desert also becomes a place that welcomes visitors from all over.